Improving Hospital Efficiency Through Data-Driven Management A Case Study of Health First, Florida - Blanchard, Janice C. (RAND Corporation, 2015)
This report presents a case study of how one health system-Health First, in Brevard County, Florida-addressed resource challenges by using Lean thinking (focusing on process improvement, affecting both structural components and operational processes) enabled by information technology.